La Ejecución del Derecho de Repetición contra las Autoridades de Elección Popular que han ocasionado Perjuicios al Estado - García Gaona, Kelvin Remigio (2017)
My thesis is oriented in the study of law of repetition, in which its conceptualization, its effects and the application form is established in order to recover the amounts paid or withdrawn by the State instituting proceedings against the authorities elected and widely to public officials, especially when it is established that the law of the State does not apply, thus harming the collective interest of society to provide providing works and services, as it directly affects the heritage State by paying inflated values given as compensation to third parties injured by the improper actions by authorities elected causing irreparable harm against administered. According to the analysis of the results of field research, it was determined that the right of recourse in our country does not accept cash, so it is left unpunished to a number of people who have been elected by popular vote so there is no appropriate regulations to implement these processes, which affect the state and society. To conclude, therefore, that there is a loophole in the legislation of our country, not established a reform proposal for effective implementation of the right of recourse against the elected authorities that have caused damage to the State and therefore the need arises to recommend a legal proposal to create establish the reform of the Organic Law on Public service in order to safeguard the interests of the State and likewise provide better service works to the community avoiding wasting large amounts of withdrawn money for the error of these officials causing damage to the State.